A Defensoria Pública e a concretização do direito fundamental à assistência jurídica: uma análise sob a perspectiva do mínimo existencial - Ramos, Hellen Cristina do Lago (2018)
Rather than proclaiming rights, the greatest challenge of the actual democratic societies is to ensure their effectiveness. There is no point in an extensive list of civil, political and social rights, if there are no instruments to implement them in practice. The fundamental right to full and free legal aid is, in this context, the principal means of access to justice for those in need. It is through free legal aid that the economic and organizational hype can demand the realization of their rights before the Judiciary. In addition to legal action, full and free legal aid is designed to protect the rights of the needy in other areas, including through extrajudicial channels (through the use of alternative means of conflict resolution), and rights education. In view of the essentiality of this right for the protection of the dignity of the human person, the present work seeks to relate it to the existential minimum, that is, to an intangible content of rights necessary to guarantee a minimum standard of dignity. Thus, as a right integral to the existential minimum, the fundamental right to legal aid must be treated as a priority public policy, which is not subject to the “under reserve of the possibilities” argument. Therefore, the proper structuring of the Public Defender, which is the institution constitutionally designed to effect the fundamental right to legal aid, should receive the same priority attention by the constituted powers